Exosomal MiR-199a-5p Inhibits Tumorigenesis and Angiogenesis by Targeting VEGFA in Osteosarcoma - Zhang, Lu; Cao, Hongxin; Gu, Guanghui; Hou, Dehui; You, Yunhao; Li, Xiang; Chen, Yunzhen; Jiao, Guangjun (Frontiers in Oncology, 2022)
Background: Osteosarcoma (OS) is the most common primary bone malignancy. microRNAs have been found to play a vital role in tumor angiogenesis. Here, we investigated the effects of miR-199a-5p on tumor growth and angiogenesis in osteosarcoma. Furthermore, the underlying molecular mechanisms and signaling pathways were explored. Methods: The datasets were extracted from the Gene Expression Omnibus and the differentially expressed miRNAs (DEmiRNAs) were screened out by the GEO2R online platform. The potential target genes were predicted using the miRTarBase database. The predicted target genes were further analyzed by Gene Ontology and pathway enrichment analysis and a regulatory network of DEmiRNAs and their target genes was constructed. The effects of osteosarcoma cell derived exosomal miR-199a-5p on the proliferation, migration and neovascularization of HUVECs were evaluated by conducting EdU assays, Transwell experiments and tube formation assays. A dual-luciferase reporter assay was performed to detect whether VEGFA was the direct target of miR-199a-5p. Furthermore, in vivo xenograft models were established to further investigate the intrinsic role of miR-199a-5p in osteosarcoma tumorigenesis and angiogenesis. Results: A total of 149 DE-miRNAs were screened out, including 136 upregulated miRNAs and 13 downregulated miRNAs in human osteosarcoma plasma samples compared with normal plasma samples. A total of 1313 target genes of the top three upregulated and downregulated miRNAs were predicted. In the PPI network, the top 10 hub nodes with higher degrees were identified as hub genes, such as TP53 and VEGFA. In addition, we found that the expression level of miR-199a-5p in exosomes derived from osteosarcoma cells was remarkably higher than the osteosarcoma cells, and the exosomes derived from osteosarcoma cells were transported to HUVECs. Overexpression of miR-199a-5p could significantly inhibited HUVEC proliferation, migration and neovascularization, whereas downregulation of miR-199a-5p expression exerted the opposite effect. The in vivo results verified that overexpression of miR-199a-5p in osteosarcoma cells could suppress the growth and angiogenesis of tumors. Conclusion: Our results demonstrated that miR-199a-5p could be transported from osteosarcoma cells to HUVECs through exosomes, subsequently targeting VEGFA and inhibiting the growth and angiogenesis of osteosarcoma. Therefore, miR-199a-5p may act as a biomarker in the diagnosis and treatment of osteosarcoma.